(untitled) (Research, Society and Development, 2023)
Aflatoxin B1 (AFLA B1) is a type of mycotoxin, considered the most carcinogenic of the group. Observed in several foods, its ingestion can lead to several pathologies or even death in the long term. Through consumption of food contaminated by humans and animals. The existing techniques for its detection are based on chromatography or ELISA. They are tools with good sensitivity, however they do not meet the needs of the food industry. Therefore, new methodologies are needed for the analysis of contaminated foods. The purpose of this work was to develop an electrochemical immunosensor to detect AFLA B1. The sensor platform was synthesized through self-assembled layers based on the adsorption of the antibody linked to zinc oxide nanoparticles coupled to cysteine on the surface of the gold electrode. Therefore, to assemble and optimize the biosystem, a study was carried out to characterize the layers, bioactivity (selectivity, sensitivity and stability) and topography of the platform. For this, electrochemical techniques, cyclic voltammetry and electrochemical impedance spectroscopy, with atomic force microscopy were used. Subsequently subjected to samples of oat flour contaminated with different concentrations of AFLA B1. The manufactured immunosensor showed a linear response between 1 μg.mL-1 to 100 μg.mL-1, and detection limit 0.95 pg.mL-1, being evaluated in both types of samples. The platform exhibited good reproducibility and high selectivity when subjected to another mycotoxin, Ochratoxin A.